Weight misperception and substance use: Brazilian Study of Cardiovascular Risks in Adolescents (ERICA) - Simoni Urbano da Silva; Vivian Siqueira Santos Gonçalves; Laura Augusta Barufaldi; Kenia Mara Baiocchi de Carvalho (BMC, 2022)
Abstract Background Adolescence is a crucial period for body image formation. Weight misperception is the discrepancy between individuals' body weight perception and their actual nutritional status. Both weight concerns and substance use are common among adolescents, and there is evidence of an associations between these two variables. Thus, the aim of this study was to assess the association between weight misperception and substance use (smoking and alcohol) in a national sample of normal weight Brazilian adolescents. Methods Data were obtained from the Brazilian Study of Cardiovascular Risks in Adolescents (ERICA), a cross-sectional, multicenter, national, school-based survey, carried out in 124 municipalities with more than 100,000 inhabitants from Brazil. The sample included adolescents aged 12-17 years, classified as normal weight by nutritional status evaluation. The following measures were collected: weight underestimation and overestimation (exposure); having tried cigarette smoking, current smoking, current alcohol consumption, binge drinking and current smoking and alcohol consumption(outcomes); macro-region, sex, type of school, and excessive screen time (confounders). The frequency of variables was calculated with 95% confidence intervals (CI). Poisson regression models were used to estimate prevalence ratios (PR). Results In total, data from 53,447 adolescents were analyzed. Weight misperception was present in a third of the adolescents, with similar prevalence of weight underestimation and overestimation. In adolescents aged 12-14 years, weight underestimation and overestimation were associated with having tried cigarette smoking (PR: 1.18 and 1.43, respectively), current alcohol consumption (PR: 1.33 for both weight misperception categories), and binge drinking (PR: 1.96 and 2.01, respectively). Weight underestimation was associated with both having tried cigarette smoking and current alcohol consumption in boys (PR: 1.14 and 1.16, respectively) and girls (PR: 1.32 and 1.15, respectively). In girls, weight overestimation was associated with all substance use variables (PR between 1.19 and 1.41). Conclusions Our results showed an association between weight misperception and having tried cigarette smoking, alcohol consumption, and binge drinking in younger adolescents. In addition, weight overestimation was associated with all substance use indicators in girls. Based on our findings, interventions aimed to improve weight perception in normal weight adolescents may contribute to the reduction of substance use in this population.